Evaluation of Exhaust Emissions of a Semi-Adiabatic Diesel Engine with Plastic Oil - Aditya Seshu Machiraju; M. V. S. Murali Krishna; P. Ushasri (Technological Innovation in Engineering Research Vol. 1, 2022)
The Exhaust emissions of the IC Engines, particularly Diesel Engines are the major constituents of Air-pollution around the globe. These emissions cause health hazards like tuberculosis, asthma, severe headache, vomiting sensation, dizziness, loss of haemoglobin, etc., when they are inhaled in. They also cause serious Environmental disorders like Green-House effect, Acid rain, Global warming etc. Hence it is important to control these emissions at any const. In the context of fast depletion of fossil fuels, ever increase of pollution levels with fossil fuels, increase of economic burden on developing countries like India, the search for alternative fuels is necessary and inevitable. Though vegetable oils have comparable properties with diesel fuel, they have high viscosity and low volatility causing combustion problems in diesel engines. Alcohols have high volatility but low Cetane number (a measure of combustion quality in diesel engine). Plastic oil derived from waste plastic by the process of pyrolysis has equitant calorific value with diesel fuel. However, its viscosity is higher than diesel fuel calls for semi adiabatic diesel engine. The concept of semi adiabatic diesel engine is to reduce heat flow to the coolant there by providing hot combustion chamber used for burning high viscous fuels like plastic oil. Semi adiabatic engine consisted of air gap insulated piston with stainless steel crown and stainless steel gasket. The Exhaust emissions of a Semi-Adiabatic Diesel Engine with Plastic Oil as fuel were evaluated at different values of Injection Timing and Injection Pressure. Injection timing was varied with electronic sensor. A Nozzle Testing Apparatus, was used to vary the Injection Pressure at 3 steps of 40 Bar, starting from 190 Bar till 270 Bar. Supercharging was employed at a pressure of 0.8 bar. The Break Thermal Efficiency (BTE) at various Injection Timings and Injection Pressures was evaluated, to determine the Optimal Injection Timing of the SADE. The Timing at which Peak BTE was obtained was identified as the Optimum Injection Timing (OIT) of SADE with Plastic Oil as fuel. The Levels of Particulate Matter, Carbon Monoxide (CO), Nitrous Oxides (NOX) and Unburned Hydrocarbons (UBHC), of an SADE with Plastic Oil, with and without Supercharging with varied injection pressure and injection timing.